Effect of the Consumption of Chocolate Enriched with Tryptophan and Resveratrol on Biochemical Markers and Oxidative Stress in a Healthy Population [Efecto del Consumo de Chocolate Enriquecido Con Triptófano y Resveratrol Sobre Marcadores Bioquímicos y de Estrés Oxidativo en Población Sana] - Florez-Mendez, J (Universidad de Antioquia, 2019)
Background: Chocolate is a product with high nutritional value, of sensory characteristics accepted and preferred by the consumer, in addition to beneficial to health. Based on the benefits attributed to cocoa components, investigations have shown that chocolate consumption has been involved in the modulation of blood pressure protection, the lipid profile, the activation of platelets, and insulin sensitivity. Objective: Evaluate the effect of consuming a tablet of chocolate enriched with tryptophan present in the peanut and resveratrol contained in the peel flour and grape seed, on biochemical markers and oxidative stress in a healthy population. Methods: The study was conducted in 10 subjects aged between 20 and 40 years, who consumed daily for 21 days, a chocolate bar of 15 g enriched with tryptophan and resveratrol. Before starting the study and after 21 days, the participants were given weighty measures, waist, hip and blood pressure. As well as blood samples, where was analyzed: Glycemia, creatinine, triglycerides, total cholesterol, HDL, LDL, VLDL, uric acid, insulin and markers of oxidative stress 8- isoprostane and catalase. The non-parametric statistical tests were applied Kruskal-Wallis for n=10, with a value of significance of 0.05. Results: A statistically significant decrease in insulin values and oxidative stress marker 8-isoprostane was stopped, whereas catalase values increased significantly. Conclusions: The consumption of chocolate enriched with tryptophan and resveratrol, does not alter the biochemical parameters of glycemia, creatinine, triglycerides, total cholesterol, HDL, LDL, VLDL and uric acid. But it significantly helps the decrease of insulin in blood and could have beneficial health effects related to the reduction of oxidative stress, after consuming 15 g of the chocolate during 21 days. © 2019, Universidad de Antioquia. All rights reserved.